Association of ambient temperature with social isolation among the community-dwelling Chinese older adults: A cross-sectional study in Hong Kong - Eliza Lai-Yi Wong; Hong Qiu; Kin-Fai Ho; Annie Wai-Ling Cheung; Hera Leung; Frank Youhua Chen; Eng-Kiong Yeoh (Heliyon)
Background: The adverse health impacts of ambient temperature have been well-documented, encompassing not only the mortality and morbidity burden but also mood and mental health disorders. However, the relationship between temperature and social isolation remains unexplored. The objective of the current study was to investigate the potential associations between ambient temperature and social isolation among the aging population. Methods: We took advantage of a cross-sectional survey conducted between January 2017 and November 2018 from a community service program special for older adults aged ≥60 who lived in a central community of Hong Kong. The personal social isolation was assessed by the validated Lubben Social Network Scale-6 (LSNS-6), with a score ranging from 0 to 30 and score of less than 12 indicating social isolation. The environmental exposures, including ambient temperature, sunshine hours, rainfalls, and air pollution, were obtained from the nearby monitoring stations. The association of ambient temperature with LSNS-6 score or social isolation was examined by the generalized linear models while adjusting the potential confounding from other environmental exposures and personal sociodemographic factors. Results: Among the 1616 participants, the distribution of LSNS-6 score was approximately normal and the mean score was a bit higher on cool days than on hot days (13.0 vs. 12.2). Compared with cool temperatures (14.4–19.5oC), the independent effect estimates of hot ambient temperatures (24.5–28.7oC) was associated with a 2.38 (95%CI: 1.63–3.13) decrease in LSNS-6 score. Meanwhile, we observed statistically significant associations of sunshine exposure, gender, health status, marital status, living alone, religion, and housing type with LSNS-6 score or social isolation. Conclusions: Our study revealed a clear association between ambient cool temperatures and reduced social isolation, as well as association between hot temperatures and social isolation among older Chinese adults residing in the urban community of Hong Kong.